ANALYTICAL THINKING SEBAGAI PROBLEM SOLVING PERUSAHAAN MODERN - Fensi, Fabianus (Jurnal Pengabdian dan Kewirausahaan, 2022)
Today, an interest in developing analytical and creative ways of thinking has become a necessity for many people as well as many companies. The root of it all is that every company has problems with organizing the various powers within the company. This is realized by PT. Serena Indopangan. Realizing the importance of analytical thinking, the company conducts an “analytical thinking” seminar for employees from the coordinator to the director level. The seminar aims to foster analytical and creative thinking of employees to solve problems in carrying out their daily work. By realizing that they have many potential strengths and complement each other's weaknesses, each company is always directed to achieve success. Everyone in the company has their own strengths and weaknesses, both in terms of physical, emotional, intellectual, talent, and spiritual aspects. Leaders must be able to maximize the strengths of their subordinates and encourage their weaknesses to complement each other so as to produce a new strength for the company's success. Success is achieved, not by the leader's egocentric way of thinking, but the ability to think from the point of view of the strengths and potentials of subordinates. The leader's job is to manage the intelligence potential of the subordinates for the betterment of the company. The ability to think analytically is the ability to manage various subordinate strengths in a comprehensive and professional manner. A good leader does not measure success based on his own strength alone, but his ability to manage the various potential intelligences possessed by all actors under his control. That is the essence of analytical thinking in dealing with problems within the company.